Robotic nephron-sparing surgery for renal tumors: Current status - Raed A Azhar; Inderbir S Gill; Monish Aron (Indian Journal of Urology, 2014)
There have been a number of advances in robotic partial nephrectomy (RPN) for renal masses. We reviewed these advances with emphasis on the evolution of technique and outcomes as well as the expanding indications for RPN. Literature in the English language was reviewed using the National Library of Medicine database. Relevant articles were extracted, and their citations were utilized to broaden our search. The identified articles were reviewed and summarized with a focus on novel developments. RPN is an evolving procedure and is an emerging viable alternative to laparoscopic partial nephrectomy and open partial nephrectomy with favorable outcomes. The contemporary techniques used for RPN demonstrate excellent perioperative outcomes. The short-term oncologic outcomes are comparable to those of laparoscopic and open surgical approaches. Further studies are needed to assess long-term oncologic control.